Pengaruh Intermitensi Radiasi Matahari Terhadap Daya Keluaran pada PLTS Terapung Studi Kasus Pulau Kodingareng, Makassar Sulawesi Selatan - Radhiansyah Radhiansyah; A. Syahrinaldy Syahruddin; Dwi Sahidin (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2025)
Photovoltaic (PV) systems are a promising renewable energy source due to their ease of installation, eco-friendliness, and abundant solar radiation availability. Indonesia has a theoretical potential of 4.625 kWh/m² and a practical potential of 3.767 kWh/kWp; however, as of September 2021, its installed capacity was only 194 MW. Land constraints have led to the development of floating PV systems, which reduce land usage and enhance module efficiency due to lower temperatures above water. Nonetheless, PV systems face challenges from solar radiation intermittency, influenced by cloud opacity, causing output power fluctuations. This study maps cloud opacity patterns on Kodingareng Island based on dry and rainy seasons using 2020 BMKG data. Results indicate that output power during the dry season is more stable than in the rainy season due to lower cloud cover. Conversely, thick cloud cover during the rainy season reduces solar radiation reaching PV modules, resulting in fluctuating power output. Thus, floating PV systems demonstrate better energy availability during the dry season. This study highlights the importance of understanding cloud opacity patterns in planning floating PV systems to address the challenges of solar radiation intermittency.